Impact of circulating current control in capacitor voltage ripples of modular multilevel converters under grid imbalances - Li, Jinke (2020)
The negative-sequence current of a modular multilevel converter (MMC) under unbalanced ac grid conditions increases the voltage ripples of the submodule capacitors. This paper investigates the impact of circulating current control in capacitor voltage ripples under different unbalanced ac grid conditions, while considering multiple control objectives and independent control of active and reactive power. It is demonstrated that higher order harmonic injection in the circulating current through a reference calculation based on instantaneous information improves operation of the MMC reducing capacitor voltage ripples at the cost of increased peak arm current and dc current oscillations. The efficacy of the circulating current control is validated through real-time digital simulations of an 800 MVA benchmark MMC high-voltage direct current transmission system.